Assessment of phagocytosis and cytokine secretions by monocytes in the presence of plasmodium falciparum - Xuan, Keh Min (2021)
Malaria remains one of the most common human infections worldwide. In endemic areas, malaria is a leading cause of morbidity and mortality and it causes significant socioeconomic burdens to the affected people. Monocytes are part of the immune system to control parasite burden and to protect host against malaria infection. Monocytes play their protective roles against malaria via phagocytosis, cytokine production and antigen presentation. Though monocytes are crucial for clearance of malaria infection, they also have been shown to cause adverse clinical outcomes. The objective of this study was to determine the morphology of P. falciparum, to assess phagocytic capability of infected red blood cells by human monocytes and further measure the cytokine secretions of monocytes following phagocytosis by using ELISA. In this study, monocytes were isolated from whole blood collected from healthy individuals while Plasmodium falciparum (3D7) was cultured under optimal conditions. Phagocytotic activity and cytokine production by the monocytes following malaria infection were assessed in vitro by co-culturing the monocytes and P. falciparum-infected red blood cells for 1 and 2 hours. The present study demonstrated that the monocytes phagocytosed the P. falciparum-infected red blood cells and the phagocytosis index increased with longer incubation time, from 8.2% at 1 hour incubation time to 10.4% (p<0.05) at 2 hours incubation time. Following phagocytosis, the monocytes produced TNF-α, initiating innate immune response to help in the clearance of parasite. The data have shown that monocytes cultured alone expressed the highest level of TNF-α during 0 and 1 hour of incubation, while co-culture of monocytes with P. falciparum-infected red blood cells produced the highest level of TNF-α after 2 hours of incubation. Comparing the trend among monocyte control, parasite control and co-culture, all showed an increase in the level of TNF-α produced in the first hour, but the concentration decreased significantly in the second hour. As a conclusion, these findings suggest that monocytes play an important role in malaria infection by phagocytosing the parasites and producing TNF-α for the removal of parasites, thereby initiating an immune response for malaria eradication.